1992
DOI: 10.1002/ijc.2910500130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of A U‐937 subline which can be induced to differentiate in serum‐free medium

Abstract: We report the selection and characterization of a U-937 subline which is capable of long-term growth in serum-free medium and can be induced to differentiate. The subline (U-937-1SF) can be maintained in standard RPMI-1640 medium supplemented by antibiotics only. As compared to the serum-dependent U-937 parental cell line, U-937-1SF produced lower amounts of lysozyme and elastase and had a decreased surface expression of complement receptor 1 (CD35) and myeloid antigens CDw17 and CD38. Apart from these alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…The kinetic properties of HL-60-uninduced cells determined by us are similar to those described by Mehdi et al (37). The potential doubling time of U937 cells resulting from the double label technique confirms previous data obtained by analysis of growth curves (38). However, in K562 cells, the potential doubling time we obtained by bivariate distributions of BrdUrd labeling versus DNA content was lower than that determined before by growth curve experiments (39).…”
Section: Discussionsupporting
confidence: 88%
“…The kinetic properties of HL-60-uninduced cells determined by us are similar to those described by Mehdi et al (37). The potential doubling time of U937 cells resulting from the double label technique confirms previous data obtained by analysis of growth curves (38). However, in K562 cells, the potential doubling time we obtained by bivariate distributions of BrdUrd labeling versus DNA content was lower than that determined before by growth curve experiments (39).…”
Section: Discussionsupporting
confidence: 88%
“…The maturation-promoting effect of 1␣,25-di-hydroxyVitamin D3 (calcitriol) on monocytic cell lines has been reported by several authors [19][20][21][22][23]. As expected, U-937 cells treated with 100 nM calcitriol for 72 h, showed many differentiation-related changes, such as an increase in CD14 and CR3 expression, lower proliferation rate, and adherence to the plastic surfaces (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…1). Oberg et al [20] reported an increase in the percentage of U-937 cells expressing CD14, but they did not show the magnitude of the increment in the cell population. We found a ninefold increase in CD14 expression after 72 h of incubation with 100 nM calcitriol.…”
Section: Discussionmentioning
confidence: 95%